Estudio para Determinar los Riesgos Laborales de tipo Psicosocial Ocasionados por el Trabajo en Casa (2023)
In the evolution and transformation of new markets, lines, products and services and in the desire to find, direct and continue with organizational projects, companies did not visualize, focus or give importance to the risks that their Workers will carry out different work activities at home, thus having future consequences on their physical and emotional state. Therefore, a bibliographic review was carried out to identify the factors associated with Psychosocial occupational risks caused by working at home, with a qualitative research focus, based on exploratory research and starting from a global theme followed by a national theme. , ending with research and local bibliographical references. Based on criteria related to the different existing variables of the problem and seeking the attention and interest of readers as the main objective. The results of this research will lead to the development of the study and the solution of the problem statement, knowing and mitigating the negative impacts on the development of work activities in a family environment and the social environment.